MAKNA MAJAS NOVEL 5 CM KARYA DONNY DHIRGANTORO KAJIAN STILISTIKA DAN IMPLEMENTASINYA - Sulis Septy Anisya; Titik Sudiatmi (Jurnal Bastra (Bahasa dan Sastra), 2024)
The research aims to study the figure of speech used in Donny Dhirgantoro’s novel, 5 Cm. The purpose of this research is to describe the types of figure of speech and the definition according to the context of Donny Dhirgantoro’s 5 Cm and its implementation of literature study for students in high school. The research is qualitative. The descriptive method used in order to obtain the description of language style. Based on the result of data analysis, it can be concluded that: (1) there are four figures of speech discovered, namely similarity, contrast, association, and repetition. The total number of figures of speech is 72. Similarity consists of 12 personifications, 13 similes, 13 metaphors; contrast has 5 hyperboles, 1 litotes, 3 antithesis; association has 3 metonymies, 1 synecdoche part pro toto, 10 synecdoche totem pro parte, 3 ellipsis; repetition consists of 1 antanaclasis, 6 repetitions, and 1 parallelism, (2) the meaning delivered through four figures of speech is varied since it depends on the context. However, the author used mostly tke personification figure of speech in order to make the story alive so that the readers will be willing be read the stories. The used of parable is the authot’s effort to create strong affection between two things compared in order to make the reader can be able to catchthe intended meanings of the author. Next, the used of metaphor figure of speech is the author’s efford to disguise the purpose of consideration for thar persong – the person in question did not feel offended, do not feel embarred or humiliated the public, and (3) the implementation of the novel of literature study for students in high school considers a) three important aspects, namely language, psychology, culture and b) syllabus, standard competence, basic competence and lesson plan.